Feasibility study of co-mixing biomass with additive waste materials for biochar high calorific value of co-firing applications - Shahmi, N. M.; Isa, M. R.; Habib, S. H.; Salmiaton, A.; Hafriz, R. S.R.M. (Elsevier B.v., 2026)
The growing demand for sustainable energy solutions and effective waste valorisation has intensified interest in producing high-energy solid biofuels from heterogeneous waste streams. This study evaluates the feasibility of co-mixing lignocellulosic biomass with selected additive waste materials such as food waste, polypropylene-based disposable facemasks, high-density polyethylene, and polyethylene to enhance the fuel properties of biochar for coal co-firing applications. Slow pyrolysis was conducted under controlled inert conditions, and the resulting biochar, bio-oil, and gas products were systematically characterised. Results show that co-mixing biomass with plastic-derived additives significantly improves biochar fuel quality. The biomass-polyethylene blend achieved the highest calorific value (24.14 MJ kg⁻¹), exceeding both raw biomass and sub-bituminous coal, while also exhibiting high fixed carbon and low ash content. Plastic-enriched blends further enhanced hydrocarbon formation in bio-oil and increased the presence of detectable combustible gas components relative to biomass alone. Overall, the findings demonstrate that co-pyrolysis of biomass with selected waste plastics offers a practical pathway for producing energy-dense biochar suitable for coal substitution, supporting waste-to-energy integration within a circular economy framework.